Conflictul generațiilor în România interbelică, Mircea Eliade și tatăl său - Liviu Bordaș (Revista de Istorie și Teorie Literară)
The article investigates for the first time Mircea Eliade’s relationship with his father, in the light of both published texts and unpublished manuscripts. The portrait of the father in Ehade’s Memoirs is contrasted with the profile emerging from the personal files of Captain Gheorghe Eliade, preserved in the Military Archives. The father-son relationship is set up against the larger relationship (and conflict) between the ”War generation“ and the ”young generation“, to which they belonged. The father’s admiration for Ion Heliade Radulescu and Mircea Eliade’s theorising of the ”conflict of generations“ bring into discussion the earlier generations: the 1848 generation and the 1880 Junimea generation. Since the name Eliade had been a choice of the father, the study dwells extensively on its significance and on the way in which the son relates to it. The theoretical part of the study considers the different types of humanism characterising the two Eliades. What defines the father is the vision of homo novus, which places the meaning of life in social ascension and in achieving fame (the ”name“) for himself and his family. The son, instead, becomes a supporter and theoretician of the idea of the ”new man”, a product not only of social and political evolution, but, first and foremost, of spiritual transformation and regeneration. Although their ideas were divergent, the son eventually achieved what the father expected of him. But then again, the idea of the new man was — after a period of political drifting — transformed into an ample vision of a new humanism.